The land and it's people - Mitchum, Robert; Martin Sandler Productions (Washington, DC : PBS Video, 1987)
Shows how the bounty of Amarica's natural resources inspired the business minds of several entrepeneurs. Concentrates on customer service, vision, opportunity, and perseverance.
Copy available in DVD format.
Keywords: Entrepreneurship -- United States; Natural resources -- United States; Entrepreneurship